Delay in presentation to hospital for childhood cataract surgery in India - Sheeladevi, Sethu (Eye (Lond), 2018)
PURPOSE: Cataract is one of the major causes of avoidable visual disability in children and the aim of this study was to investigate the age at which children with cataract present for surgery at tertiary hospitals across India. METHODS: A prospective multicenter study collected data from 9 eye hospitals in 8 states in India. All children admitted for cataract surgery between Nov 2015 and March 2016 were considered eligible. Parents were interviewed at the hospital by trained personnel and socio demographic information, age at diagnosis and at surgery and the relevant clinical data were obtained from the medical records. Mean age, age range at surgery were used and performed logistic regression analyses. RESULTS: Parents of 751 consecutive cases were interviewed, of which 469(63%) were boys and 548 (73%) were from rural areas. Cataract was bilateral in 493 (66%) and unilateral in 258 (34%); of the unilateral cases, 179 (69%) were due to trauma. The mean age at surgery for ‘congenital’ and ‘developmental’ cataract was 48.2 ± 50.9 and 99.7 ± 46.42 months, respectively and the mean age was lower in the southern region compared to other regions. Children with 2 or more siblings at home were five times more likely to undergo surgery within 12 months (OR, 4.69; 95% CI: 2.04–10.79; p = < 0.001). CONCLUSIONS: Late surgery for childhood cataract remains a major challenge and the factors determining this issue in India are pertinent also to several other countries and need to be addressed for every child with cataract to achieve full visual potential.